MARINE MANAGEMENT AND THE SITING OF ELECTRICAL GENERATING STATIONS ON TROPICAL SHORELINES - Coles, Stephen L. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Expanding utilization of electricity by developing tropical nations will produce increasing amounts of waste heat that will, in most cases, be disposed into natural water systems. Such disposal represents a serious potential marine management problem for nations which intensively utilize the nearshore marine environment in their subsistence economy. This communication reviews the marine environmental effects resulting from thermal disposal at three generating stations on the Island of Oahu, Hawaii and compares these with results of similar studies made elsewhere in the tropics and subtropics. Conclusions are drawn from these studies concerning desirable environmental features to be considered for thermal outfalls in tropical areas, and some environmental consequences of alternative methods of cooling water treatment are discussed.